2022
DOI: 10.1590/0001-3765202120201562
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of The Effect of Extracellular Vesicles Isolated from Mouse Embryonic Fibroblasts on Wound Healing in an Experimental Diabetic Mouse Model

Abstract: This study aimed to investigate the effects of Extracellular Vesicles (EV) secreted from mouse embryonic fi broblasts EV on wound healing of full-thickness skin defect in a diabetic mouse model. The study included both in vitro and in vivo experimental studies 82 mice. In the in vitro stage of the experimental study, hysterectomy was performed on two mice between the 13-14th days of pregnancy and then EV was isolated by cell culturing.VEGF, IL-6, and TNF-α biomarkers were examined in tissue homogenate. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…In present study, we successfully demonstrated wound healing properties of EGTE in rabbit model via gross findings, oxidative stress, connective tissue markers, pro-inflammatory markers and expression of growth markers which are considered as most important parameters for medicinal preparations having wound healing potential [ 7 , 9 , 11 ]. In recent times researchers have proposed that biomedical preparations obtained from biologics having abundant concentration of growth factors can accelerate wound healing in diabetic patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In present study, we successfully demonstrated wound healing properties of EGTE in rabbit model via gross findings, oxidative stress, connective tissue markers, pro-inflammatory markers and expression of growth markers which are considered as most important parameters for medicinal preparations having wound healing potential [ 7 , 9 , 11 ]. In recent times researchers have proposed that biomedical preparations obtained from biologics having abundant concentration of growth factors can accelerate wound healing in diabetic patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals diagnosed with diabetes face an increased risk of developing diabetic ulcers, a perplexing and highly distressing complication that further complicates their diabetes management [ 9 , 10 ]. The healthcare costs associated with treating these diabetic ulcers impose a substantial economic burden on patients, and these ulcers also exhibit a high recurrence rate, affecting approximately 50 % of diabetic individuals [ 11 , 12 ]. Researchers have identified several factors contributing to impaired diabetic wound healing, including reduced blood vessel formation, impaired skin cell regeneration, hindered fibroblast migration, and elevated levels of Tumor Necrosis Factor alpha (TNF-α) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under normal physiological condition, EVs derived from dermal fibroblasts promote diabetic cutaneous wound healing through the Akt/β-catenin pathway ( 10 ). Another report showed that EVs isolated from mouse embryonic fibroblasts augmented the effect of VEGF, promoting angiogenesis in the wound area ( 11 ). Gangadaran et al ( 12 ) have already confirmed the angiogenic cargoes in human fibroblast-derived EVs.…”
Section: Introductionmentioning
confidence: 99%